Access to markets for smallholder farmers in Alto Molócue and Molumbo, Mozambique: Baseline report of a survey conducted as part of an impact evaluation of the INOVAGRO II project - Erman, Alvina; Ghebru, Hosaena; Mogues, Tewodaj (International Food Policy Research Institute, 2016)
This report presents the data from a baseline data collection effort as part of the impact evaluation of Phase II of the Innovation for Agribusiness (INOVAGRO II) intervention in northern Mozambique. INOVAGRO II is a development program intended to decrease rural poverty by improving the connectedness of farmers to market systems. The baseline data were collected before the intervention began in two districts in Zambezia province – Alto Molócue and Molumbo – during the months of August and September 2015. The questionnaire focused on agricultural production and market access, in particular on the INOVAGRO value chain crops – soybean, pigeon pea, and maize. The purpose of the report is to describe the data, focusing on key variables.